Association between kinking of the cervical carotid or vertebral artery and ischemic stroke/TIA - Wang, Junjie; Lu, Jun; Qi, Peng; Li, Chunwei; Yang, Ximeng; Chen, Kunpeng; Wang, Daming (Frontiers in Neurology, 2022)
Introduction Kinking of the cervical carotid or vertebral artery is a commonly structural abnormality in patients with cerebrovascular disease. However, there is no consensus about the relationship between kinking and ischemic stroke/ TIA. We aim to determine the effect of arterial kinking on ischemic stroke/ TIA. Methods A retrospective study was performed on patients who underwent cerebral angiography with DSA between January 2014 and December 2018. Demographic information and comorbidities were recorded. Each anatomic circulation system was defined as an observation unit. Kinking and stenosis of each circulation unit were recorded. Ischemia stroke or TIA within 6 months and its location was assessed as an outcome. Logistic regression with a generalized estimating equation approach was used for analysis. Results A total of 1062 patients (mean age 57.9±14.5 years, 740 males and 322 females) were included in the study. Of the patients, 369 (35%) had kinking and 771 (73%) had ischemic stroke/ TIA. There were 110 left anterior, 90 right anterior, and 308 posterior circulation units, among which 343 had mild, 160 had moderate, and 243 had severe kinking. Multivariate regression analysis showed that ischemic stroke/ TIA was associated with severe kinking (OR 1.39, 95% CI 1.03-1.88, P=0.03). Posterior circulation was more vulnerable to acute ischemia than left anterior and right anterior circulation (OR 3.58, 95% CI 2.81-4.56, P<0.0001). Conclusion Severe kinking of the cervical carotid or vertebral artery may be associated with a higher risk of ischemic stroke/ TIA, especially when the kinking is located in posterior circulation.